Penatalaksanaan Holistik Dispepsia Fungsional Kronik pada Ny.S 56 Tahun yang Berulang dalam 1 Tahun Terakhir Melalui Pendekatan Kedokteran Keluarga - Caesaria Zuya; Diana Mayasari (CV. Jasa Sukses Abadi, 2022)
yspepsia is one of the health problems that are often encountered in daily practice. Dyspepsia was defined as having one or more symptoms of epigastric pain, burning, fullness after eating, or early satiety. Bloating and nausea are common with dyspepsia but are not specific. Potential lifestyle factors associated with dyspepsia include smoking, alcohol, and consumption of analgesics. Furthermore, dietary habits that include consumption of fast food, salty foods, coffee/tea, and spicy foods are associated with aggravating dyspepsia symptoms and lack of physical activity may contribute to the onset of dyspepsia. In addition, the stress factor is also something that must be overcome because it is one of the trigger factors and also aggravates the condition of dyspepsia patients. This study is a case report. Primary data were obtained through history taking (autoanamnesis and alloanamnesis from family and patients), physical examination, supporting examinations and home visits to assess the physical environment. Assessment based on a holistic diagnosis from the beginning, process, and end of the study qualitatively and quantitatively. Application of family doctor services based on evidence based medicine to patients by identifying risk factors, clinical problems, and patient management based on a patient problem solving framework with a patient centered approach and a family approach. A 56-year-old female patient came to the Kemiling Health Center with complaints of abdominal discomfort such as pain and a lump in the gut, accompanied by nausea and headache that had worsened since 2 days ago. Complaints are felt to come and go but get worse if the patient is late to eat. Similar complaints have been felt to have disappeared since 2017. Management of functional dyspepsia patients in a holistic and comprehensive manner, patient centers, family approved with functional dyspepsia treatment regularly according to EBM is needed in order to eliminate symptoms, trigger factors and change patient behavior so as to prevent complications and recurrence of the disease.